Effect of Intra-Canal Calcium Hydroxide Remnants on the Push-Out Bond Strength of Two Endodontic Sealers - Ghabraei, Sholeh; Bolhari, Behnam; Yaghoobnejad, Fatemeh; Meraji, Naghmeh (Iranian Endodontic Journal, 2017)
Introduction: The aim of this study was to evaluate the effect of intra-canal calcium hydroxide (CH) remnants after ultrasonic irrigation and hand file removal on the push out bond strength of AH-26 and EndoSequence Bioceramic sealer (BC Sealer). Methods and Materials: A total of 102 single-rooted extracted human teeth were used in this study. After root canal preparation up to 35/0.04 Mtwo rotary file, all the specimens received CH dressing except for 34 specimens in the control group. After 1 week, the specimens with CH were divided into 2 groups (n=34) based on the CH removal technique; i.e. either with ultrasonic or with #35 hand file. Then specimens were divided into two subgroups according to the sealer used for root canal obturation: AH-26 or BC Sealer. After 7 days, 1 mm-thick disks were prepared from the middle portion of the specimens. The push out bond strength and failure mode were evaluated. Data were analyzed by the two-way ANOVA and Tukey’s post hoc tests. Results: The push out bond strength of both sealers was lower in specimens receiving CH. These values were significantly higher when CH was removed by ultrasonic (P<0.05). The dominant mode of failure in all subgroups was of mixed type except for the BC Sealer specimens undergoing CH removal with hand file which dominantly exhibited adhesive mode of failure. Conclusion: CH remnants had a negative effect on the push out bond strength of AH-26 and BC Sealer. Ultrasonic irrigation was more effective in removing CH. Keywords: AH-26; Calcium Hydroxide; Endosequence BC Sealer; Push-Out Bond Strength